Understanding the awareness, knowledge, and opinion of dairy cattle welfare among dairy farmers in Keningau, Sabah - Sadiq, Mohammed Babatunde; Lin, Sim Song; Ramanoon, Siti Zubaidah; Syed Hussain, Sharifah Salmah; Shaik Mohamed Mossadeq, Wan Mastura; Salisi, Mohd Shahrom; Mansor, Rozaihan (MDPI, 2021)
This study aimed to assess the knowledge and opinions about DCW among dairy cattle farmers in Keningau, Sabah. A questionnaire was developed, validated, and administered by hand to 30 farmers. The data collected include farmers’ and farm demographics, and opinions regarding the criteria and indicators of DCW. Only 17 respondents (57%) had heard of “dairy cattle welfare” before this study. Nine farmers (30.0%) had poor knowledge about DCW criteria, whereas 13 (43.7%) and 8 (26.7%) farmers had satisfactory and good knowledge, respectively. Farmers with higher education, larger herd size, high production level, and exotic cattle breeds showed a better understanding. Farmers understood most of the indicators; however, opinions regarding cattle behavior during milking, their physical appearance and their lying down behaviour need to be improved. Nevertheless, 28 respondents ranked their animals’ welfare as either good or satisfactory, which further reflects a poor implementation of DCW measures. The main factors suggested by farmers to influence DCW in their herds were facilities, worker issues, management practices, and animal well-being. In conclusion, guidance from veterinarians and animal welfare specialists may be needed to improve the farmers’ understanding and practices of DCW.